Susceptibility Pattern of ESBL Urine Specimens in Non-Intensive Care Room at Ulin General Hospital - Alicia Fitri Wulandhany; Dewi Indah Noviana Pratiwi; Noor Muthmainah; Agung Biworo (Indonesian Association of Clinical Pathologist and Medical laboratory, 2021)
Beta-lactam antibiotic resistance can occur in ESBL-producing bacteria such as E.coli and K.pneumoniae, which can cause UTI. One of the risk factors for infection is the non-intensive care space density level. The objective of this study was to determine the sensitivity pattern of ESBL-producing bacteria in urine specimens of patients in the non-intensive care of Ulin General Hospital, Banjarmasin, in the period of 2016-2018. A descriptive study with a cross-sectional design using data results of urine culture and antibiotic susceptibility patterns data in non-intensive care patients at Ulin General Hospital from 2016 to 2018. The urine test results showed 96 positive isolates of ESBL-producing bacteria, consisting of ESBL-E.coli (69.8%) and ESBL-K.pneumonia (30.2%). Antibiotics with low sensitivity tests were Penicillin, Cephalosporin, Monobactam, and Penicillin/beta-lactam inhibitor combinations. Contrastingly, antibiotics with high sensitivity were Aminoglycoside, Carbapenem, and Glycylcycline. It was concluded from this study that the ESBL-producing bacteria in urine specimens for non-intensive care patients of Banjarmasin Ulin General Hospital in the period of 2016-2018 showed varying sensitivity to antibiotics